The comparative benefits and drawbacks of equity-based investment versus token-based investment models in achieving scalability and profitability for startups (in the US) - Peled, Omri; de Batz de Trenquelléon, Laure Sabine Marie; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This research examines the comparative benefits and drawbacks of equity-based investment versus token-based funding models, particularly in the US market, as it is the biggest hub of financing, both VC and ICO based startups.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses